Factors Associated With Orthostatic Hypotension In The Elderly In Anambra State - K.G, Dr Enwonwu; C, Prof Ibeh; I, Prof Modebe; E, Prof Owoaje; Zoakah, Prof A.I.; C, Dr Ifeadike; N, Dr Ezeama; E, Dr Azuike (Journal of Medical Biomedical and Applied Sciences, 2018)
see the pdf